GE_GERICHTE C/17378/2010 vom 3. Dezember 2012 - GE Cour de justice (2012)
BAIL À LOYER; MAJORATION DE LOYER; FORMULE OFFICIELLE; ENRICHISSEMENT ILLÉGITIME ; SOUS-LOCATION | CC.2.2 CO.269d CO.270.2 CO.269.a.b CO.62